New species and records of bioluminescent Mycena from Mexico. (4th March 2019) - Cortés-Pérez, Alonso; Desjardin, Dennis E.; Perry, Brian A.; Ramírez-Cruz, Virginia; Ramírez-Guillén, Florencia; Villalobos-Arámbula, Alma R.; Rockefeller, Alan
ABSTRACT: Seven species of bioluminescent fungi are recorded from the cloud forests in Mexico. Six represent new species belonging to the genus Mycena, whereas Mycena globulispora is a new distribution record for the country. Descriptions, illustrations, photographs, and an identification key to bioluminescent fungi species from Mexico are provided. Sequences of nuc rDNA internal transcribed spacer (ITS1-5.8S-ITS2 = ITS) region were generated for barcoding purposes and comparisons with similar species.